Active hybrid common mode filter for a highly integrated on-board charger for automotive applications - Schmenger, J.; Kramer, R.; März, Martin (2015 IEEE 13th Brazilian Power Electronics Conference and 1st Southern Power Electronics Conference, COBEP/SPEC 2016, 2015)
In this paper an active hybrid common mode filter is proposed. The active filter network is used to reduce the conducted CM emissions caused by a highly integrated 3.7 kW on-board charger (OBC) for electric vehicles (EV). To show the volume benefits of the hybrid filter, a discrete filter which meets the IEC 61000-3-2:2006 standard is used for comparison. As a result of the presented measures, the active filter circuit adds more than 12 dB attenuation to the common mode filter at the design frequency. The volume of the common mode chokes of the EMI filter can be reduced by 40 % compared to the chokes of the discrete filter.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Active filter; electromagnetic interference; on-board charger